To die in style! : the residential lifestyle of feasting and dying In Iron Age, Stamna, Greece - Christakopoulou-Sōmakou, Gioulika (Archaeopress Publishing Ltd, 2018)
This volume investigates the culture of feasting and the rituals of death among elite citizens in Iron Age Stamna, Greece, by studying archaeological finds from a large number of Protogeometric era tombs.